Prediction of pork supply via the calculation of pig population based on population prediction model - Zhang, Fan; Wang, Fulin (International Journal of Agricultural and Biological Engineering, 2020)
Based on the perspective of pig population system prediction, and accorded to principle of pig months transfer, this paper refers to the modeling principle and method of discrete population quantity prediction model. Then the prediction model of pork supply is derived and established: Firstly, the recursive model of pig population system and estimation model of pork supply was established. Then this study estimated the sum of monthly mortality and culling rate of breeding sows. Furthermore, the method for new left gilts in each month and estimation of breeding sows at each month of age was established. Last, this research established the estimation method model of the initial state of pig population. On this basis, an example calculation is made to predict the monthly pork supply in Heilongjiang Province from January 2016 to March 2018 in the future. The results showed that the prediction model of pork supply based on the prediction of pig population system is an effective perspective to study the forecast of pork supply. In the prediction stage, the prediction accuracy of the number of slaughtered fattened hogs was 96.36% and 97.54%, and the prediction accuracy of pork supply was 98.08% and 93.82%.This study not only lay a theoretical foundation for further study on the balance between pork supply and demand, but also helps to guide pork producers and governments at all levels to make relevant production decisions and plans. Keywords: pig population, breeding sow, pig production, pork supply prediction, population prediction model DOI: 10.25165/j.ijabe.20201302.5303 Citation: Zhang F, Wang F L. Prediction of pork supply via the calculation of pig population based on population prediction model. Int J Agric & Biol Eng, 2020; 13(2): 208–217.